Presidential Decree-Law No. 128/2014 On Amending The Penal Code - Egypt (2025)
presidential Decree-Law No. 128 of the year 2014 On Amending The Penal Code قرار رئيس مجلس جمهورية مصر بالقانون رقم 128 لسنة 2014 بشأن تعديل قانون العقوبات